Tanggung Jawab Sosial Perusahaan dalam Pengelolaan Konflik Irigasi Pertanian (Studi Kasus di Desa Wangen Kabupaten Klaten Indonesia) - Dhea Firna Ananda; Bekti Wahyu Utami; Agung Wibowo (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Corporate Social Responsibility (CSR) programs have significant potential to support irrigation resource management in the agricultural sector, especially in addressing conflicts between farming communities and companies. The first objective of this study is to analyze the optimization of CSR programs in mitigating irrigation conflicts, and the second objective is to evaluate the impact of CSR on agriculture in Wangen Village, Polanharjo District, Klaten Regency. Conflicts between farmers and companies arise over various issues, which create social tension, erode farmers' trust in companies, and reduce agricultural productivity. Using a qualitative case study approach, data were obtained through in-depth interviews, participatory observation, and documentation with 13 informants, including farmers, CSR representatives from PT Tirta Investama, the NGO Gita Pertiwi, the village government, extension workers, and community leaders. The results show that CSR plays a role in four important aspects, namely program planning, activity implementation, funding provision, and decision-making and conflict resolution, which are carried out through several stages, namely problem identification, multi-party mediation involving NGOs as third parties, and the implementation of programs to improve irrigation channels and strengthen community institutions. CSR interventions have had positive impacts, such as increased agricultural productivity, improved water distribution, the restoration of social relations between farmers and companies, and increased solidarity through cooperation. However, the sustainability of CSR programs still requires the strengthening of local institutions. PT. Tirta Investama's CSR is a strategic instrument in mitigating resource conflicts and supporting community-based food security. This study aims to contribute to the development of a participatory, agribusiness-based CSR model and to strengthen the synergy among the private sector, farmer institutions, and village governments in the fair and sustainable management of water resources.